Measures to affect the elimination behaviour of fattening pigs in a conventional housing system - Höne, Ulrike; Schrader, Lars; Hölscher, Richard; Traulsen, Imke; Krause, E. Tobias (Frontiers in Animal Science, 2024)
Pigs try to separate their lying area from the dunging area. However, due to several factors such as pen design, increasing ambient temperatures, or lack of space, pigs often lie in the dunging area or defaecate in the lying area, resulting in increased pen and animal soiling. Besides poor hygienic conditions, this may also lead to increased ammonia emissions. Thus, proper changes to support the structure of conventional pens may help facilitate better elimination behaviour of pigs and establish and maintain their functional areas, including dunging areas. In this study, we investigated the effect of measures to help pigs use pre-defined functional areas. The study was done on a conventional farm in pens with fully slatted floors. Pen and animal soiling was recorded by a scoring scheme in a total of 37 pens during two fattening periods. In the first fattening period (baseline period), the pen design remained unchanged to evaluate the status quo. In the second fattening period (treatment period), certain changes in 16 test pens were done to structure the pen into a designated dunging and a resting area. The remaining 21 pens served as control pens. Changes included installation of LED spotlights, partly open pen partitions, and re-arrangement of nipple drinkers and hay racks. To compare the soiling of pens, the difference in pen soiling was calculated both between the baseline and the treatment periods and the control and test pens. As a first step, the difference in pen soiling between the control and test pens within both fattening periods was compared. Additionally, to control for changes in pen soiling over time, the differences between the pen soiling of the control pens during the baseline period and the treatment period were compared. The same comparison was done for the test pens. In the treatment period, no significant difference in the pen soiling between the control pens and test pens was found. However, over time, i.e., comparing the soiling of test pens and control pens between the baseline and the treatment periods, pigs soiled the designated dunging areas more in the treatment period. The fattening pigs in both the test and the control pens were very clean during both fattening periods. Our pen modification treatment that combined changes in LED spotlights, drinker locations, roughage locations, and partly open pen partitions did not result in clear effects. However, we can not rule out that these features can help to structure the pens in a positive way.